Grads at work : a webpage by undergrads for undergrads - Chan, Jacinta Kum Ling (2009)
Grads at Work was an idea conceived by four final-year undergraduates of the School of Communication Studies. For many of us, graduating with a degree represents the culmination of many years of education, hard work and toil, Hence, as this milestone in life beckons, many undergraduates embark on their frantic search for employment. For some, this search for a good-paying job may start as early as 12 months before the actually graduation. Others take their time and start looking after the final exams. But “kiasu” or otherwise, undergraduates will begin to give the recruitment advertisemcnts more than a cursory glance and wonder how to start formatting their resumes for the first time in their lives. This report highlights the rationalisations behind the conception of Grads at Work and how the project aims to provide a service that fulfils the needs of undergraduates. The report also details the entire process of setting up Grads at Work from idea conceptualisation to the final delivery. Finally, it also tells of our vision and hopes for the project in the future.